2009
DOI: 10.4067/s0034-98872009000300014
|View full text |Cite
|
Sign up to set email alerts
|

Función respiratoria en la senectud

Abstract: 3 mmHg per year) which is attenuated to become almost undetectable over the age of 70 (Rev Méd Chile 2009; 137: 411-8).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 25 publications
1
3
0
8
Order By: Relevance
“…In this study, the elderly presented maximal respiratory pressures with lower values than the ones predicted for the age 12 , which corroborates the studies [18][19][20][21][22] showing that respiratory muscle strength is lower among the elderly. After training, it was possible to observe the significant increase of MIP and MEP in both groups, which suggests that these therapies were efficient, as previously observed by Kotz 23 , however, involving healthy young subjects.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the elderly presented maximal respiratory pressures with lower values than the ones predicted for the age 12 , which corroborates the studies [18][19][20][21][22] showing that respiratory muscle strength is lower among the elderly. After training, it was possible to observe the significant increase of MIP and MEP in both groups, which suggests that these therapies were efficient, as previously observed by Kotz 23 , however, involving healthy young subjects.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies 4,18,19,21,22 also found that respiratory muscle strength showed reduced compared with expected values for older adults, according to the equation regarding age and sex 13 . With advancing age, the reduction in respiratory muscle strength is similar to the reduction in the strength of the skeletal muscles, especially after 60 years of age 21 .…”
Section: Discussionmentioning
confidence: 99%
“…No sistema respiratório, ocorre redução lenta e progressiva da complacência da parede torácica, do aumento da resistência das vias aéreas, 16 tendo início a sarcopenia, definida como o declínio progressivo de massa muscular, força e qualidade de contração. 15 Oyarzun 16 destaca que a sarcopenia ocorre em função da hipoplasia das fibras musculares, alterações nos neurônios periféricos, além de modificações intrínsecas à célula: no transporte de cálcio nas fibras musculares, redução do ATP mitocondrial e redução na síntese de miosina de cadeia pesada.…”
Section: Discussionunclassified